Combined kinetic analysis of solid‐state reactions: The integral method (ICKA). Issue 12 (24th August 2020) - Casal, M.D.; Marbán, Gregorio
Abstract: In this work, we propose the first I ntegral method for the C ombined K inetic A nalysis (ICKA) of solid‐state reactions typically performed in a thermogravimetric analyzer. The ICKA method prevents the systematic inaccuracies inherent to all the differential methods, including the standard CKA method. Two main achievements have been made for implementing the method: (1) the most accurate approximation for the general temperature integral yet developed, and (2) a general integral form of the kinetic model of the type g (α) = ( abcZ ) −1 [1 − (1 − α a ) b ] c, where Z is a parameter evaluated together with the preexponential factor and a, b, and c are fitting parameters. This expression allows any known kinetic model to be exactly or very closely reproduced. Together, the two developments yield an equation for the conversion, α, that has been successfully fitted to simulated conversion values of single‐step reaction processes following different kinetic models. The curve fitting resulted in the same values of the kinetic and model parameters as those from which the simulated conversion curves were originally built, proving the validity of the ICKA method.